Que nous dit la végétation de la cohérence spatiale, biologique et paysagère de la « ceinture verte » de la région Île-de-France ? - Fabien Roussel (Projets de Paysage)
Due to insufficient content, the green belt project of the Ile-de-France region has remained largely unknown to local stakeholders and the general public. We would like to demonstrate that in spite of many development projects for green spaces in suburban areas at a local level, the green belt lacks coherence spatially. Signifying an alternative to a dense and supposedly grey urban environment the colour green invites us to study vegetation and subsequently semi-natural planted and landscaped spaces. By clearly outlining the different scales and defining an interconnected typology of fringe landscapes we propose a method and criteria based on plant bio-geography establishing the links between modes of land occupation, flora and landscape, thus making it possible to envisage vegetation for urban fringes and the unfinished green belt project in a new light.